Literature Review : The Effectiveness of Blueberries as a Diet Menu for Adolescents - Ferrynda, Tiara Putri; Najah, Salwa Maziatun; Safitri, Yuliana; Andyarini, Esti Novi (International Conference on Sustainable Health Promotion, 2023)
Blueberries are a powerful source of fiber that fills you up without consuming excess calories. Although blueberries are a good source of fiber and can help provide a feeling of fullness, it is still important to maintain a balance in food consumption and overall nutrition. A healthy and balanced diet will include a variety of foods and nutrients, not just relying on one type of food. This study is to deepen researchers’ knowledge regarding blueberry fruit nutrition for a healthy diet menu in adolescents and review the results of previous research that is related to the research that we will conduct. In writing this article using the narrative method in reviewing and analyzing the results of previous studies. The articles used in this study only come from one database, namely Google Scholar with the criteria for a 5-year publication range, namely from 2018 to 2022 with the type of review article and in full text form. The results of the study show that people show an interest in consuming blueberries because of their antioxidant polyphenol content which plays a role in controlling the process of obesity and inflammation. Intake of blueberries in the diet can reduce body weight, glucose, cholesterol, triglyceride, and adenosine levels in obese male subjects. Even in women, blueberries only lower adenosine levels without affecting weight, glucose and triglyceride levels. Research has also shown that adding blueberries to the diet of healthy. older adults can improve cognitive function, especially in challenging cognitive tests. In addition, blueberries have also been shown to increase factors related to bone formation. Blueberries have a variety of health benefits, including controlling obesity, improving cognition, reducing the risk of gestational diabetes, and protecting the bones and heart from oxidative damage. Consuming blueberries can be a great addition to a healthy and colorful diet.